2014
DOI: 10.1186/1752-1947-8-202
|View full text |Cite
|
Sign up to set email alerts
|

Nonabsorbable suture granuloma mimicking ovarian cancer recurrence at combined positron emission tomography/computed tomography evaluation: a case report

Abstract: IntroductionThis is the first case of suture granuloma mimicking isolated ovarian cancer relapse. Only six analogous cases have been previously reported in other malignancies.Case presentationWe report the case of a 44-year-old Caucasian woman with partially platinum-sensitive ovarian cancer in which radiological features, including computed tomography and combined 18F-fluorodeoxyglucose-positron emission tomography/computed tomography, were strongly suggestive of isolated cancer relapse in her right subdiaphr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 13 publications
(18 reference statements)
0
17
0
Order By: Relevance
“…Therefore, it causes a significant inflammation in tissues. For this reason, it should be remembered that reaction may develop against silk suture material (16,17).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it causes a significant inflammation in tissues. For this reason, it should be remembered that reaction may develop against silk suture material (16,17).…”
Section: Discussionmentioning
confidence: 99%
“…To date, numerous case studies related to suture granuloma have been reported by different departments, including cases of suture granuloma that occurred after open repair of Achilles tendon rupture (Ergin, Demirel, & Özmen, ) and after thyroidectomy (Abdul Hamid, Yu‐Lin, & Maharani Hassan, ; Soylu et al, ), cases mimicking ovarian cancer recurrence (Imperiale, Marchetti, & Salerno, ), and cases that occurred shortly after gastrectomy and lymphadenectomy (Tsujita et al, ). However, to our knowledge, no case of suture granuloma after varicocelectomy has been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the high accuracy of positron emission tomography (PET)/CT scanning, this method may produce false-positive results in cases of foreign body granuloma, possibly as a consequence of localized inflammation mimicking malignant tissue glucose uptake (14). Imperiale et al (8) reported the case of a patient with ovarian cancer where combined 18 F-fluorodeoxyglucose PET/CT suggested isolated cancer relapse. However, the lesion was surgically removed and demonstrated to be a foreign body granuloma (8).…”
Section: Discussionmentioning
confidence: 99%
“…Imperiale et al (8) reported the case of a patient with ovarian cancer where combined 18 F-fluorodeoxyglucose PET/CT suggested isolated cancer relapse. However, the lesion was surgically removed and demonstrated to be a foreign body granuloma (8).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation